The Role of the Airway and Gut Microbiome in the Development of Chronic Lung Disease of Prematurity - Lieve Boel; David J. Gallacher; Julian R. Marchesi; Sailesh Kotecha (Pathogens, 2024)
Chronic lung disease (CLD) of prematurity, a common cause of morbidity and mortality in preterm-born infants, has a multifactorial aetiology. This review summarizes the current evidence for the effect of the gut and airway microbiota on the development of CLD, highlighting the differences in the early colonisation patterns in preterm-born infants compared to term-born infants. Stool samples from preterm-born infants who develop CLD have less diversity than those who do not develop CLD. Pulmonary inflammation, which is a hallmark in the development of CLD, may potentially be influenced by gut bacteria. The respiratory microbiota is less abundant than the stool microbiota in preterm-born infants. There is a lack of clear evidence for the role of the respiratory microbiota in the development of CLD, with results from individual studies not replicated. A common finding is the presence of a single predominant bacterial genus in the lungs of preterm-born infants who develop CLD. Probiotic preparations have been proposed as a potential therapeutic strategy to modify the gut or lung microbiota with the aim of reducing rates of CLD but additional robust evidence is required before this treatment is introduced into routine clinical practice.